Effect of Ecoenzyme Addition to Red Glutinous Rice-Based Trichoderma asperellum on Bujang Marantau Germination Biomass - Lega Pesona Kasih; Azwir Anhar (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Enhancing rice productivity is essential to meet increasing national food demands, especially for local varieties such as Bujang Marantau from Tanah Datar District. This variety is highly valued for its yield potential and pest resistance; however, it faces challenges related to declining seed quality. This research investigates the effect of incorporating an ecoenzyme into a Trichoderma asperellum formulation, using a red glutinous rice medium, on the germination and early growth of Bujang Marantau rice. The study employed a Completely Randomized Design (CRD) with eight ecoenzyme concentrations (0%, 10%, 20%, 30%, 40%, 50%, 60%, and 70%) and four replications. The measured parameters were the fresh and dry weights of seedlings at seven days after germination. Data were analyzed using ANOVA at a 5% significance level, followed by DNMRT when significant differences were detected. The results indicated that ecoenzyme application significantly affected seedling fresh weight during germination but did not influence dry weight. A 30% ecoenzyme concentration was found to be the most effective in promoting germination biomass. This finding demonstrates that ecoenzyme incorporation at this optimal concentration enhances Bujang Marantau rice seedling vigor and represents a promising approach for improving seed quality. Further research is recommended to evaluate field performance and the long-term effects on productivity.